1997
DOI: 10.1002/pen.11777
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, mechanical, and adhesive properties of thermoplastic‐LCP blends filled by glass fibers

Abstract: Rheological, mechanical, and adhesive properties have been studied of two‐phase polymer blends containing a liquid crystal copolyester of poly(ethylelene terephthalate) and p‐hydroxybenzoic acid plus isotactic polypropylene (PP) with varying compositions and concentrations of glass fibers. Perfect fibrillation of the disperse LC‐phase into the PP‐matrix in capillary flow was observed at LCP concentrations >20 wt% and temperatures >488 K. This effect leads to a decrease of blend viscosity and a reinforcing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…From what has been said in preceding sections it may be suggested that fibrillization of isotropic PMMA melt due to LCP presence exerts the reinforcing effect. In this relation this system differs from the polypropylene-LCP blends, 11 probably due to stronger interactions between PMMA and LCP and higher adhesion strength at the interface between components. Really, the strength of adhesion bonds between polypropylene and LCP is 1.25 MPa, 11 whereas between PMMA and LCP 3.1 MPa (unpublished data).…”
Section: Rheological Characteristics At Harmonic Vibrationsmentioning
confidence: 84%
See 2 more Smart Citations
“…From what has been said in preceding sections it may be suggested that fibrillization of isotropic PMMA melt due to LCP presence exerts the reinforcing effect. In this relation this system differs from the polypropylene-LCP blends, 11 probably due to stronger interactions between PMMA and LCP and higher adhesion strength at the interface between components. Really, the strength of adhesion bonds between polypropylene and LCP is 1.25 MPa, 11 whereas between PMMA and LCP 3.1 MPa (unpublished data).…”
Section: Rheological Characteristics At Harmonic Vibrationsmentioning
confidence: 84%
“…In this relation this system differs from the polypropylene-LCP blends, 11 probably due to stronger interactions between PMMA and LCP and higher adhesion strength at the interface between components. Really, the strength of adhesion bonds between polypropylene and LCP is 1.25 MPa, 11 whereas between PMMA and LCP 3.1 MPa (unpublished data). Figure 11 gives the dependencies of the mechanical characteristics of solid extrudates on the whisker concentration for pure components and PMMA /LCP blend 7/3.…”
Section: Rheological Characteristics At Harmonic Vibrationsmentioning
confidence: 84%
See 1 more Smart Citation
“…This is because of the low viscosity of TLCP attribute to the structure consist of linear semirigid rod-like molecules that can improve the processability of composites system and extend into fibrous structures and orient in the flow direction. 5,6 Many studies related to hybrid composites reinforced with fiber and TLCP, the matrix polymers such as polypropylene (PP), [7][8][9] high density polyethylene, 10 Polycarbonate (PC), 11 etc. had been done.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of inorganic fillers not only enhanced the mechanical properties of the blends but also reduced the anisotropy of the resulting materials [5]. Rheological characterization revealed that TLCP could reduce the melt viscosity of glass-filled thermoplastics [6]. Much work has been published on TLCP systems containing different inorganic solid reinforcements, such as glass fibres [7], carbon black [8], whiskers [9] and silica [10].…”
Section: Introductionmentioning
confidence: 99%